Entropic Phase Transitions with Stable Twisted Intermediates of Bio‐Inspired Self‐Assembly. Issue 43 (13th September 2016) - Tao, Kai; Levin, Aviad; Jacoby, Guy; Beck, Roy; Gazit, Ehud
Abstract: Controlling the hierarchical process and capturing the intermediate stage underlying bio‐inspired self‐assembly are pivotal for understanding their aggregation mechanism and exploring possible applications. Here, the self‐assembly of a designed minimal lipopeptide was characterized, showing it to initially self‐assemble to narrow nanotwists, which then ripen to wide nanotwists, and finally transit to hollow nanotubes. The supramolecular phase transitions were revealed to be driven by entropic hydrophobic interactions, rather than by the common mechanism of enthalpy‐related contributions. The transformation dynamics were sufficiently slow to enable detection and characterization of each stage, thus inducing the stable and extensive distributions of twisted intermediates. The findings allow an in‐depth understanding of the hierarchical self‐association of bio‐inspired building blocks and provide a new approach for the preparation of superstructures of unique morphologies. Abstract : Haste makes waste ! A simple lipopeptide composed of a FK dipeptide sequence conjugated to a myristic acid chain, named C14 ‐FK, was designed to initially self‐assemble to narrow nanotwists, which then ripen to wide nanotwists, and finally transit to hollow nanotubes in a kinetically slow manner. The entropic phase transformations endow new understanding of processes underlying bio‐inspired self‐assembly and fabrication of superstructures with unique morphologies.